The changing role of high dose melphalan with stem cell rescue in the treatment of newly diagnosed multiple myeloma in the era of modern therapies—back to the future!. Issue 1 (March 2020) - Kazandjian, Dickran; Dew, Alexander; Hill, Elizabeth
Abstract: State of the art treatment for myeloma involves using 3-drug combinations incorporating immunomodulatory drugs (IMiDs) and proteasome inhibitors (PIs). Clinical trials for 4-drug combinations incorporating monoclonal antibodies added to IMiD and PI based backbones are underway. Recent retrospective analyses show that patients who attain MRD negativity have similar long term outcomes regardless of early or delayed high dose melphalan with autologous stem cell support (HDM-ASCT). Given HDM-ASCT toxicity, not "overtreating" would be beneficial. Short of data from future prospective clinical trials addressing the question of the role of HDM-ASCT in MRD negative patients, varying expert opinions inherently arise. In this paper, we present the historical context of HDM-ASCT and data supporting 3-drug combinations. We then propose that a viable option for patients who reach MRD negativity is to transition to maintenance therapy directly without early HDM-ASCT, and reserving stem cell harvest to cases where HDM-ASCT is a possibility at relapse.